The Impact of Initial Ability and Learner Interest on Learning Outcomes in Project Based Learning (PjBL) - Ulfi Lathifah; Aswardi Aswardi; Yeka Hendriyani; Ari Syaiful Rahman Arifin (STKIP Singkawang, 2025)
This study aims to explore the impact of learners' initial ability and interest on learning outcomes in project-based learning (PBL). With the Systematic Literature Review (SLR) approach, it is a systematic research approach to identify, evaluate, and analyze literature or research relevant to a particular topic in an objective and structured manner. This study analyzed 35 journals that discussed the effect of initial ability and interest on student learning outcomes in project-based learning. The results show that higher initial ability makes it easier for students to absorb the material and develop practical skills such as problem solving. On the other hand, high interest encourages students' active engagement and motivation in the project, which contributes to improved learning outcomes. This study also identified that a mismatch between students' initial abilities and the PjBL approach can reduce the effectiveness of learning. These findings provide important insights for educators to design more effective learning that adapts to students' needs, and support more comprehensive curriculum planning. Project-based learning is expected to enhance 21st century skills such as creativity, collaboration and problem solving, which are relevant to prepare students for real-world challenges.